Shkodra Lake: Social and Environment Problems - Alushi, Violeta (Richtmann Publishing, 2012)
The human activity is considered as the main reason for the damage of the lake ecosystem stability. Shkodra Lake isecologically characterized by a high stability. Clean water and high productivity are considered as potential health factors of this Lake.This ecosystem is one of the most preserved wetlands of the Mediterranean. However, the unfavorable global factors and human activityhave a dangerous impact on the ecosystem. The damage of the lake water regime causes oscillations, which lead to disorders for thehabitats and ecosystem, creating concerns to the life of populated areas. Contamination from decomposing organic matter degrades theecosystem in a trophic unrecoverable situation. Destruction of forests around watershed, failure to have anticorrosive measures andwastewater discharges are essential for the growth of solid flows affecting the eutrophism of the lake. Shkodra Lake can’t support thesedifficult situations by itself alone. It leads to water microbial contamination of beaches and increases people's concerns. Awarenessshould be raised to the public, decision making, and the population around it, in order to eliminate these risk factors. Crosscontamination with toxic substances penetrate the food chain of biota and end up accumulated up to the humans, causing life -threatening and deadly diseases. People should be aware and should take measures to eliminate discharges to ensure the standards oflake water and consuming resources. Long-term strategies and policies should be set up for developing the Lake region, with mainobjectives and measures of managing character. Natural ecosystem of Shkodra Lake and the urban ecosystem of Shkodra city willcoexist in a better way if harmony and integration of natural development and human activity will be achieved.